Experiences with a Generator Tool for Building Clinical Application Modules - Kuhn, K.A.; Lenz, R.; Elstner, T.; Siegele, H.; Moll, R. (Methods of Information in Medicine, 2003)
Objectives: To elaborate main system characteristics and relevant deployment experiences for the health information system (HIS) Orbis®/ OpenMed, which is in widespread use in Germany, Austria, and Switzerland.Methods: In a deployment phase of 3 years in a 1.200 bed university hospital, where the system underwent significant improvements, the system’s functionality and its software design have been analyzed in detail. We focus on an integrated CASE tool for generating embedded clinical applications and for incremental system evolution. We present a participatory and iterative software engineering process developed for efficient utilization of such a tool.Results: The system’s functionality is comparable to other commercial products’ functionality; its components are embedded in a vendor-specific application framework, and standard interfaces are being used for connecting subsystems. The integrated generator tool is a remarkable feature; it became a key factor of our project. Tool generated applications are workflow enabled and embedded into the overall data base schema. Rapid prototyping and iterative refinement are supported, so application modules can be adapted to the users’ work practice.Conclusions: We consider tools supporting an iterative and participatory software engineering process highly relevant for health information system architects. The potential of a system to continuously evolve and to be effectively adapted to changing needs may be more important than sophisticated but hard-coded HIS functionality. More work will focus on HIS software design and on software engineering. Methods and tools are needed for quick and robust adaptation of systems to health care processes and changing requirements.
Keywords: Clinical information systems; health information systems; software design